Using Simulation as Project-Based Learning to Improve Students’ Speaking Skill on Business English Course - Avinta Ika Nurrahma; Saifuddin; Siti Nafi’yah (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
The aim of this study is to know the increasing students’ speaking ability by using simulation as project-based learning on business English course. This research used classroom action research with a combination of simulation method as project-based learning on the Business English course. The use of simulation has been implemented on the Business English course at Faculty of Economics, management study program at Kadiri Islamic University. Sixth-semester students performed presentations as simulations and practiced speaking in groups. This research was conducted in two research cycles which the average score of students' speaking performance increased significantly significant from 58.23 to 67.65. Students also have a positive perception to this method which most of students agree that simulation can provide motivation, simulation is a fun way of learning, and simulations provide learning experiences and provide more value from learning self-study. Students’ perception of project-based learning indicate that this method can improve their speaking performance. By the combination of simulation methods as project-based learning, students' speaking ability can increase.